Toxicity of Granules of Bintaro Leaf Extract (Cerbera odollam Gaertn.) on Armyworm (Spodoptera litura Fab.) - Ahmad Habib Sholahuddin; Wachju Subchan; Jekti Prihatin (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2018)
Grayak caterpillar is insect pests that become pests of various food crops. Grayak caterpillars cause a decrease in crop productivity and even crop failure if they are not controlled. Pest control using chemical pesticides has many adverse effects on the environment. To minimize the occurrence of environmental damage, then it is used pest control using vegetable insecticides. Bintaro Leaf (Cerbera odollam Gaertn.) is potential as a vegetable insecticide. The purpose of this study was to examine the toxicity of granule from Bintaro leaf extract (C. odollam Gaertn.) on armyworms (S. litura Fab.). This research was a laboratory experimental research using Completely Randomized Design (CRD). Serial concentrations used in this study were 0% (control), 0.5%, 1%, 1.5%, 2%, and 2.5%. The results of this study showed that the granules of Bintaro leaf extract (C. odollam Gaertn.) were effective in causing mortality of armyworms (S. litura Fab.) at 1.5% concentration by 60% and included in toxic category. The value of LC50-48 hour granule from Bintaro leaf extract (C. odollam Gaertn) was 1.41%. Keywords: Spodoptera litura Fab. , Granula extract of Cerbera odollam Gaertn., Vegetable Insecticide.